Repeated pulses of volcanism drove the end-Permian terrestrial crisis in northwest China - Dal Corso, J; Newton, RJ; Zerkle, AL; Chu, D; Song, H; Song, H; Tian, L; Tong, J; Di Rocco, T; Claire, MW; Mather, TA; He, T; et al. (Nature Research, 2024)
The Permo-Triassic mass extinction was linked to catastrophic environmental changes and large igneous province (LIP) volcanism. In addition to the widespread marine losses, the Permo–Triassic event was the most severe terrestrial ecological crisis in Earth’s history and the only known mass extinction among insects, but the cause of extinction on land remains unclear. In this study, high-resolution Hg concentration records and multiple-archive S-isotope analyses of sediments from the Junggar Basin (China) provide evidence of repeated pulses of volcanic-S (acid rain) and increased Hg loading culminating in a crisis of terrestrial biota in the Junggar Basin coeval with the interval of LIP emplacement. Minor S-isotope analyses are, however, inconsistent with total ozone layer collapse. Our data suggest that LIP volcanism repeatedly stressed end-Permian terrestrial environments in the ~300 kyr preceding the marine extinction locally via S-driven acidification and deposition of Hg, and globally via pulsed addition of CO2.